Growth rate of pterocymbium javanicum in four months period - Mohd Rafien, Muhammad Hazwan (2016)
Replanting of shade-tolerant species in open areas requires shading. Natural shading in the form of shade trees may provide the best solution. Selection of potential indigenous tree species as shade trees is important because in the past, exotics, such as Acacia mangium had been used. Therefore, this study was carried out in Universiti Putra Malaysia to elucidate the potential of Pterocymbium javanicum (melembu) shade tree. The aim of this study was to evaluate the growth performance of P. javanicum trees planted in line in two blocks. Tree growth data acquisition began in November 2015 through February 2016. The following parameters were measured, namely height of the tree, tree diameter breast height (DBH), crown height and crown diameter. The results showed a significant correlation (P <0.05) between annual tree growth, tree diameter and height of trees. There is a relationship between light intensity and the performance parameters of plant growth and physiology of trees. Melembu has a potential to serve as shade trees due to its high tree growth and crown diameter at the age of two years.